2016
DOI: 10.1038/srep31554
|View full text |Cite
|
Sign up to set email alerts
|

De Hass-van Alphen and magnetoresistance reveal predominantly single-band transport behavior in PdTe2

Abstract: Research on two-dimensional transition metal dichalcogenides (TMDs) has grown rapidly over the past several years, from fundamental studies to the development of next generation technologies. Recently, it has been reported that the MX2-type PdTe2 exhibits superconductivity with topological surface state, making this compound a promising candidate for investigating possible topological superconductivity. However, due to the multi-band feature of most of TMDs, the investigating of magnetoresistance and quantum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 28 publications
12
39
2
Order By: Relevance
“…The maximum reported values for the MR are 1.75 × 10 6 % for WTe 2 [56] and 7.5 × 10 4 % for MoTe 2 [15] (T = 2 K and μ 0 H = 9 T). Under the same conditions, for PdTe 2 (isostructural to HfTe 2 ) prepared from high-purity elements a rather low maximum MR of ∼150% was reported [57]. Hence, it can be concluded that besides the actual electronic band structure, the purity of the materials and the crystal quality determine the MR value.…”
Section: A Ambient Pressurementioning
confidence: 77%
“…The maximum reported values for the MR are 1.75 × 10 6 % for WTe 2 [56] and 7.5 × 10 4 % for MoTe 2 [15] (T = 2 K and μ 0 H = 9 T). Under the same conditions, for PdTe 2 (isostructural to HfTe 2 ) prepared from high-purity elements a rather low maximum MR of ∼150% was reported [57]. Hence, it can be concluded that besides the actual electronic band structure, the purity of the materials and the crystal quality determine the MR value.…”
Section: A Ambient Pressurementioning
confidence: 77%
“…More recently, the transition metal dichalcogenides (TMDs) TMX 2 (TM=Pd, Pt; X=Se, Te) were proposed to host type-II Dirac fermions and were soon verified in angle-resolved photoemission spectroscopy (ARPES) experiments. [17][18][19][20][21][22][23][24][25][26][27][28] Interestingly, PdTe 2 also superconducts below T c =2 K and the Au substitution can boost T c to a maximum value of 4.7 K, making this family of TMDs a promising platform to search for topological superconductors. [29][30][31][32][33][34] However, the Dirac points reported in these materials are located deeply below the Fermi level, with a binding energy of 0.6 eV in PdTe 2 , 0.8 eV in PtTe 2 , and 1.2 eV in PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the magnetoresistance and magnetization measurements of both PtTe 2 and PdTe 2 have been reported in the last year [24,31], detailed information about the Fermi surface topography extracted from angular dependence of bulk measurements like the de Haasvan Alphen (dHvA) and Shubnikov-de Haas (SdH) effects along with a comparison with Density Functional Theory (DFT) calculations are still missing. Notice for instance, that the initial report on the dHvA-effect in PdTe 2 revealed just a few Fermi surface cross-sectional areas, e.g.…”
Section: Introductionmentioning
confidence: 99%